JavaFX [ a beginner's guide - DiMarzio, J. F. (McGraw-Hill, 2011)
"Create immersive, interactive environments for any platform. JavaFXTM: A Beginner's Guide begins by explaining the technology behind JavaFX and quickly moves on to installing the JavaFX development environment and tools, including the JavaFX SDK, the Java SE JDK, and NetBeans. Then, you?ll learn how to develop desktop, browser, and mobile applications with ease. The book covers effects and transformations, animation, events, and Swing components. Techniques for creating custom nodes, embedding video and music, using JavaFX layouts, and styling with CSS are also discussed"-- Provided by publisher